2010
DOI: 10.1159/000314051
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients with Occipital Encephalocele

Abstract: Background: An encephalocele is a herniation of the brain and the meninges through a skull defect protruding towards the exterior. The condition is not rare when compared to spinal dysraphisms, but the worldwide incidence is not precisely known. The cases involving occipital encephaloceles which we have diagnosed in our clinic and the surgical approaches for this rare condition are presented herein. Methods: Thirty patients who were diagnosed with occipital encephaloceles and referred to our Neurosurgery Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 15 publications
3
65
0
3
Order By: Relevance
“…3,5,17,22,27,34 The prognosis for a newborn with an encephalocele depends on a number of factors and includes the location, size, and contents of the encephalocele, along with microcephaly and associated anomalies. 4,16,27,34 A significant proportion of these children lack normal developmental milestones and may have neurological problems such as ataxia, visual impairment, mental and growth retardation, and seizures. 22 Previous studies report that prognosis for patients with occipital and parietal encephaloceles is directly related to the presence of neural tissue, hydrocephalus, microcephaly, and accompanying cerebral malformations.…”
mentioning
confidence: 99%
“…3,5,17,22,27,34 The prognosis for a newborn with an encephalocele depends on a number of factors and includes the location, size, and contents of the encephalocele, along with microcephaly and associated anomalies. 4,16,27,34 A significant proportion of these children lack normal developmental milestones and may have neurological problems such as ataxia, visual impairment, mental and growth retardation, and seizures. 22 Previous studies report that prognosis for patients with occipital and parietal encephaloceles is directly related to the presence of neural tissue, hydrocephalus, microcephaly, and accompanying cerebral malformations.…”
mentioning
confidence: 99%
“…Factors well known to determine the prognosis of patients diagnosed with occipital encephaloceles include the size of the sac, neural tissue content, hydrocephaly, infection, and pathologies that accompany this condition [13]. In this case, although the size of the sac was bigger than ever reported before and neural tissue was also involved, we experienced a better immediate postoperative outcome, perhaps because of the larger amount of remaining functional brain mass after the surgery.…”
Section: Discussionmentioning
confidence: 69%
“…There are some factors that may influence the prognosis of patients with meningoencephalocele, The size of the herniated sac and the amount of brain tissue it contains determine the prognosis of these patients. Frontoethmoidal meningoencephalocele appears to have better prognosis [3]. Zuckerman et al reported that the reoccurrence of such cases after the initial surgery was approximately 16% with an average of 7 month interval between the first surgery and the reoccurrence [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hydrocephaly, infections, and other anomalies accompanying the condition determine the prognosis as well. The mortality rate approaches 30% despite the applied appropriate treatments [3].…”
Section: Introductionmentioning
confidence: 99%